Exosomes in lung cancer: a role in early diagnosis - Zhou, Tong; Ma, Hui; Li, Zhikang; Xu, Yijun; Zhao, Lingling (Frontiers in Oncology, 2025)
Lung cancer is the most prevalent and deadly malignant tumor in the world. Traditional treatment methods rely on histopathological analysis of cancer cells obtained through tissue biopsies, which carry risks due to their invasive nature. Thus, there is an urgent need to identify effective and non-invasive early screening methods for lung cancer. Exosomes, a crucial element of liquid biopsies, have emerged as a promising alternative due to their non-invasive collection, convenience and cost-effectiveness in diagnosing lung cancer. Research has underscored the role of exosomes in lung cancer invasion, metastasis, immune regulation, and the tumor microenvironment. Furthermore, the contents of exosomes, such as miRNAs, lncRNAs, circRNAs, and proteins, demonstrate considerable potential for the early diagnosis of lung cancer. This article provides a comprehensive review of the role and application of exosomes as liquid biopsy markers for early diagnosis of lung cancer, emphasizing their promise in improving patient outcomes through earlier detection and intervention.